A Five-Year Retrospective Study of Foot-and-Mouth Disease Outbreaks in Southern Africa, 2014 to 2018 - Elliot Mpolokang Fana; Sununguko Wata Mpoloka; Melvin Leteane; LaToya Seoke; Kelebogile Masoba; Mokganedi Mokopasetso; Aobakwe Rapharing; Tshephang Kabelo; Patricia Made; Joseph Hyera (Veterinary Medicine International)
Foot-and-mouth disease (FMD) virus (FMDv), like other ribonucleic acid (RNA) genome viruses, has a tendency to mutate rapidly. As such, available vaccines may not confer enough cross-protection against incursion of new lineages and sublineages. This paper is a retrospective study to determine the topotypes/lineages that caused previous FMD outbreaks in 6 southern African countries and the efficacy of the current vaccines to protect cattle against them. A total of 453 bovine epithelial tissue samples from 33 FMD outbreaks that occurred in these countries from 2014 to 2018 were investigated for the presence of FMDv. The genetic diversity of the identified Southern African Type (SAT)-FMD viruses was determined by comparing sequences from outbreaks and historical prototype sequences. Of the 453 samples investigated, 176 were positive for four FMDv serotypes. Out of the 176 FMD positive cases there were 105 SAT2 samples, 32 SAT1 samples, 21 SAT3 samples, and 18 serotype O samples. Phylogenetic analysis grouped the SATs VP1 gene sequences into previously observed topotypes in southern Africa. SAT1 viruses were from topotypes I and III, SAT2 viruses belonged to topotypes I, II, III, and IV, and SAT3 viruses were of topotypes I and II. Vaccine matching studies on the field FMDv isolates produced r1-values greater than or equal to 0.3 for the three SAT serotypes. This suggests that there is no significant antigenic difference between current SAT FMD vaccine strains and the circulating SAT serotypes. Therefore, the vaccines are still fit-purpose for the control FMD in the region. The study did not identify incursion of any new lineages/topotypes of FMD into the sampled southern African countries.